Factors influencing big-bubble formation during deep anterior lamellar keratoplasty in keratoconus. Issue 5 (26th August 2015) - Feizi, Sepehr; Javadi, Mohammad Ali; Daryabari, Seyed-Hashem
Abstract : Purpose: To investigate recipient and operative factors that can influence the rate of achieving a bare Descemet's membrane (DM) during deep anterior lamellar keratoplasty (DALK) for keratoconus. Materials: In this retrospective comparative study, a total of 290 (153 right) consecutive eyes from 257 (179 male) keratoconus-affected patients who underwent DALK with the big-bubble technique were enrolled. Univariate analyses and multiple logistic regressions were used to investigate factors including patient age and sex, family history of keratoconus, history of contact lens wear or vernal keratoconjunctivitis, the presence of Vogt's striae or superficial stromal opacities, keratometric readings, corneal diameter, central and peripheral corneal thickness, anterior chamber depth, vitreous length, and trephination size, which could predict achievement of a bare DM. Results: The surgery was completed as a DALK in 289 of 290 eyes, and a bare DM was successfully achieved in 229 (79.2%) eyes. The recipient sex and trephination size significantly influenced the success rate of big-bubble formation. Females had decreased odds of achieving a bare DM by 0.44 times (p=0.02). For each 0.1 mm increase in the trephination size, the odds of a successful big-bubble formation increased by 1.36 times (p=0.03). Other investigated factors did not significantly influence the rate of achieving a bare DM. Conclusions: The rate of successful big-bubble formation was 79.2% in keratoconus. Among the different factors, recipient sex and trephination size significantly influenced this rate. Females had a lower probability of big-bubble formation, and a large trephination size was associated with an increase in the probability of achieving a bare DM.